الضريبـــــــــــــة البيئيـــــــــة ودورها في الحد من التلوث البيئـــــــــــــــي (Journal of Accounting and Financial Studies ( JAFS ), 2020)
Despite the growing interest in the subject of the environment and environmental pollution and the increasing of scientific studies to measure the environmental cost, but it still suffers shortcomings and incompleteness due to the difficulties facing the process of measuring of these costs , Due to lack of the possibility of determining the monetary value to it.             The research began trying to develop solutions to the problem of the research , which is the actual measuring nothingness of environmental pollution for research sample plant and It’s comparison to local and international environmental pollution standards , for the purpose of adoption in the imposition of environmental taxes , by proposing a framework for environmental taxes (taxes on pollution) and its practical application of contaminated facilities to reduce the pollution to reach the permissible locally and internationally limits  To Protect the community and the environment from its risks and threats.The researcher was based her research to achieve the aim of the research to the following hypothesis:-          "The Actual Measurement of environmental pollution for research sample plant and It’s comparison to local and international environmental pollution standards provide relevant information can be adopted as the basis for the imposition of environmental taxes".This research include four axises. First axis reach for research approach, second axis specialize to environmental taxes , third axis seclude to the applicative part , fourth axis specialize to the important conclusions and recommendations.